Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I need to find the values of $a$ and $n$ in the following

$$ (1 + ax)^n = \sum_{i=0}^\infty \binom{2i}{i}x^i$$

How can I compare things and show that $a=-4$ and $n = -{1 \over 2}$. It's easy to expand $1 \over \sqrt{1 -4x}$ see that it's valid but I'm looking other way around.

share|improve this question
    
You can see that $n$ is not an integer. If it were, then the left hand side would be a polynomial, while the right hand side is an infinite sum of monomials. –  Michael Albanese Oct 2 '12 at 9:30
    
yeah i know that ... but how to show that $n=-1/2$ –  Santosh Linkha Oct 2 '12 at 9:45
2  
@Michael: You can see $n$ is not a positive integer –  Henry Oct 2 '12 at 10:05
    
Looking for another way around is rather strange. Unless you've already studied the series in the RHS quite a bit, there is no reason to assume it would be a (fractional) power of a binomial at all, or even satisfy any algebraic equation involving polynomials. –  Marc van Leeuwen Oct 2 '12 at 10:17
    
@Henry: Yes, you are correct, I missed that. –  Michael Albanese Oct 2 '12 at 10:18
show 2 more comments

3 Answers

up vote 1 down vote accepted

$$(1+ax)^{n}=\sum_{n=0}^{\infty}C_{2n}^{n}x^{n}=\sum_{n=0}^{\infty}\frac{(2n)!}{n!n!}x^{n}$$ Derivated at both sides, we get the first equation: $$na(1+ax)^{n-1}=\sum_{n=1}^{\infty}\frac{n(2n)!}{n!n!}x^{n-1}$$ Derivated at both sides of the first equation, we get the second equation: $$n(n-1)a^{2}(1+ax)^{n-2}=\sum_{n=2}^{\infty}\frac{n(n-1)(2n)!}{n!n!}x^{n-2}$$ Let $x=0$ in above two equations, we can get that: $$na=2\,\,\text{and}\,\,n(n-1)a^{2}=12$$ then solve the equation and we can get that $a=-4$ and $n=-\frac{1}{2}$.

share|improve this answer
    
It would be a good thing to note that, while we are using the same variable names (namely $n$) both on the left and on the right side of the equations, for one to derive that $na = 2$ and $n(n-1)a^2 = 12$, as you did, you have to consider that, on the RHS, when setting $x = 0$, you need the coefficients to be already known to be constant---not involving the variable $n$ of the LHS. –  rbrito Nov 14 '12 at 14:56
add comment

You can show that the sum is the solution of a differerential equation (try to express the derivative in function of the sum itself).

share|improve this answer
2  
could you please elaborate!! –  Santosh Linkha Oct 2 '12 at 9:09
add comment

At first, consider the series $\sum_{n=0}^{\infty}C_{2n}^{n}x^{n}$, as $\frac{C_{2n+2}^{n+1}}{C_{2n}^{n}}=\frac{4(2n+1)}{2n+2}$, we can judge that the series convergent in $[-\frac{1}{4},\frac{1}{4})$.

Note $f(x)=\sum_{n=0}^{\infty}C_{2n}^{n}x^{n}=\sum_{n=0}^{\infty}\frac{(2n)!}{n!n!}x^{n}$, then $f(0)=1$, $$f^{\prime}(x) =\sum_{n=1}^{\infty}\frac{(2n)!}{n!(n-1)!}x^{n-1} =\sum_{n=0}^{\infty}\frac{(2n+2)!}{(n+1)!n!}x^{n} =\sum_{n=0}^{\infty}\frac{(4n+2)(2n)!}{n!n!}x^{n}$$ $$xf^{\prime}(x) =\sum_{n=1}^{\infty}\frac{(2n)!}{n!(n-1)!}x^{n} =\sum_{n=0}^{\infty}\frac{n(2n)!}{n!n!}x^{n}$$ $$(1-4x)f^{\prime}(x)=2\sum_{n=0}^{\infty}\frac{(2n)!}{n!n!}x^{n}=2f(x)$$ then solve the last ordinary differential equation, we get $f(x)=\frac{c}{\sqrt{1-4x}}$, as $f(0)=1$, so $f(x)=\frac{1}{\sqrt{1-4x}}$, i.e. $\sum_{n=0}^{\infty}C_{2n}^{n}x^{n}=\frac{1}{\sqrt{1-4x}}, x\in[-\frac{1}{4},\frac{1}{4})$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.